Problems facing public school principals in Jordan in managing educational crises in light of the corona pandemic from their point of view - Aljarab’ah, Nariman Mohammad (Journal of Educational and Psychological Sciences, 2021)
The study aimed at the problems facing public school principals in Jordan in managing educational crises in light of the Corona pandemic from their point of view. In public schools affiliated to the First Zarqa Directorate in Jordan, the results of the study showed a problem facing government school principals in Jordan in managing educational crises in light of the Corona pandemic, obtaining an overall average (3.78 out of 5) with a degree of severity (high).
Keywords: problems, school principals; first blue; management of educational crises; corona regulation